Lithuanian Editions of Daniel Gottlieb Settegast’s Books on Bees as a Case of Cultural Transfer - Sidabraitė, Žavinta (Senoji Lietuvos literatūra, 2026)
Daniel Gottlieb Settegast (1741–1813), a graduate of the University of Königsberg who came from the territory that is now Poland, worked as a teacher at the school in Prökuls (Lith. Priekulė) from 1763 until his death. At the end of the eighteenth century, he compiled and published three versions of a beekeeping textbook: two in German and one in Lithuanian. These were books intended for popular education. In the mid-nineteenth century, Simonas Daukantas adapted Settegast’s textbook for the residents of Lithuania Major, also for the purpose of public education. Applying the methodology of cultural transfer, this article examines these two Lithuanian editions of Settegast’s book on bees as examples of the adaptation of the ideas of popular enlightenment (German: Volksaufklärung) to different cultural contexts. Settegast was involved in the popular enlightenment movement that gained popularity in Prussia in the second half of the eighteenth century: while working as a teacher in Prökuls, he joined the East Prussian Society for Physics and Economics, which was dedicated to promoting public education. With its support, he wrote and published Bienencatechismus (The Bee Catechism, Königsberg, 1795), a highly popular book about bees in German. Three years later, a slightly revised second German edition of Settegast’s book was published under the title Das Wahre und Nützliche in der Bienen-Zucht (Reliable and Useful Beekeeping Tips, Königsberg, 1798). Another three years later, a Lithuanian version of the book on bees, prepared by Settegast himself – Naudingos Bicʒû Knygeles (Useful Books on Bees, Königsberg, 1801) – was published. It was based on the first German edition of 1795. Having prepared the Lithuanian version of his book, Settegast acted as an agent for conveying the ideas of popular enlightenment to the community of Lithuanian peasants in Prussia. The content of the presentation and the format of the material were tailored to the standards set by the educational books of the popular enlightenment movement. The most significant transformation Settegast undertook was linguistic in nature, that is, the rewriting of the book in clear and vivid Lithuanian that was easily understood by the peasants. Both the German and Lithuanian editions sought to combat the superstitions that permeated the peasant mindset, encouraged critical thinking (common sense), fostered personal responsibility, and explained the principles of sound farming. The main body of the book provides general information about bees, their physiology, the organisation of life in a hive, practical advice on beekeeping, hive construction, honey harvesting, and honey use. Two illustrations created by the author himself are glued in the book. With a few minor proofreading corrections, this edition of Settegast’s book was reprinted in Königsberg in 1820. Nearly thirty years later, in 1848, Simonas Daukantas republished the book under the title Naudinga bĩttiû knygelė (A Useful Bee Book) in St Petersburg. Daukantas transformed the text: he adapted the orthography and language to the written tradition of Lithuania Major, thereby adapting Settegast’s book to the cultural context of Lithuania Major. Also, he adapted Settegast’s book to the changing cultural climate of the nineteenth century. Daukantas achieved this by writing a preface that captured the spirit of Romanticism. Like Daukantas’s historical works, the preface asserts a close connection between the forests that ensured the region’s prosperity in ancient times and the freedom of the people: with the destruction of one, the other was lost as well. Bees, the free creatures of thriving forests, became a metaphor for freedom in Daukantas’s preface: with the disappearance of the forests, the beekeeping skills that had been an integral part of the indigenous culture of the free Lithuanians (Samogitians) also became obsolete. Lithuanians were forced to learn about modern, cultured beekeeping from foreigners. Daukantas’s preface imparted a new meaning to Settegast’s book on bees, which had set out with modest goals of people’s enlightenment: it became not only a source of practical knowledge, but also a manifestation of longing for freedom of an oppressed nation.